Synthesis and Antimicrobial Evaluation of New 6 and7 Substituted Derivatives of Coumarin - A. Muften, Rouaa; Y.Saour, Kawkab; A.Razzak Mahmood, Ammar (Iraqi Journal of Pharmaceutical Sciences, 2017)
A series of benzohydrazide derivatives attached to coumarin moiety at position 6 and 7 have been synthesized. The reaction of coumarin derivatives (coumarin I and II) with p-nitrophenyl hydrazine yield Schiff bases (compound1a and IIa).These Schiff bases were refluxed with benzoyl chloride to give benzohydrazide derivatives of coumarin substituted at its 6 or 7 nucleus position (Ia1 and IIa1).The reaction and the purity of the products were checked by thin layer chromatography (TLC). The structures of the final compounds and their intermediates were confirmed by their melting points, infra red spectroscopy, and elemental microanalysis(CHN).Compounds (Ia1 and IIa1) were evaluated for their preliminary antibacterial and antifungal activities. Compound (IIa1) has good antibacterial activity against Staphylococcus aureus other than bacterial species, and was equivalent to ofloxacin as (standard drug).Key word: Coumarin, Schiff base, benzohydrazide derivatives, antimicrobial activity.